A Correlational Study between Listening, Structure, and Reading Comprehension of TOEFL - Nurhalimah; Randhi Nanang Darmawan (Journal of Language, Communication, and Tourism, 2022)
TOEFL as Test of English as Foreign Language is common test used in many countries an all over the world. The main objective of this study was to investigate the correlation between listening, structure, and reading comprehension in TOEFL. In this research, there were several questions regarding the three variables including listening, reading, and grammar that were focusing on the correlation between them. There were 30 students of Tourism and Business Management Department of Politeknik Negeri Jember, from whom the data was gathered, who were selected to be the sample. Quantitative method with Pearson Product Moment Correlation to prove whether there was a significant correlation among the three variables used in this research as statistical analysis. Based on the problem formulation, it can be concluded that there was significant correlation between the variables of listening, structure, and reading comprehension skills of the students of Tourism and Business Management at Politeknik Negeri Banyuwangi. For the correlation between listening and structure, the correlation coefficient was 0.642 which was considered as high. The moderate degree of correlation was found for the correlation between listening and reading with the correlation coefficient of 0.474. However, it was found that the correlation between structure and reading comprehension was weak with the correlation coefficient of 0.511. From the results of the study, it can be concluded that listening, structure, and reading comprehension in TOEFL were inter-correlated.